Functional dynamics of primate cortico-striatal networks during volitional movements - Santos, Lucas M.; Opris, Ioan; Hampson, Robert E.; Godwin, Dwayne; GERHARDT, GREG A.; Deadwyler, Sam (Frontiers in Systems Neuroscience, 2014)
The motor cortex and dorsal striatum (caudate nucleus and putamen) are key regions in motor processing but the interface between the cortex and striatum is not well understood. While dorsal striatum integrates information from multiple brain regions to shape motor learning and habit formation, the disruption of cortico-striatal circuits compromises the functionality of these circuits resulting in a multitude of neurologic disorders, including Parkinson’s disease. To better understand the modulation of the cortico-striatal circuits we recorded simultaneously single neuron activity from four brain regions, primary motor and sensory cortices, together with the rostral and caudal segments of the putamen in rhesus monkeys performing a visual motor task. Results show that spatial and temporal-task related firing relationships between these cortico-striatal circuit regions were modified by the independent administration of the two drugs (cocaine and baclofen). Spatial tuning and correlated firing of neurons from motor cortex and putamen were severely disrupted by cocaine and baclofen on correct trials, while the two drugs have dramatically decreased the functional connectivity of the motor cortical-striatal network. These findings provide insight into the modulation of cortical-striatal firing related to movement with implications for therapeutic approaches to Parkinson’s disease and related disorders.